1999
DOI: 10.1677/joe.0.1630199
|View full text |Cite
|
Sign up to set email alerts
|

Selective exocytosis of zymogen granules induces non-parallel secretion in short-term cholecystokinin-stimulated rats

Abstract: Parallel studies on pancreatic enzyme secretion and zymogen granule enzyme composition have been carried out in rats subjected to infusion of cholecystokinin (CCK) (1·25 µg/kg per h) over 30 min. Flow cytometric analysis showed a significant decrease in the mean value of granule size after CCK stimulation. The amount of trypsinogen stored in each individual zymogen granule was significantly lower at 30 min of CCK infusion, but no variation in intragranular amylase content was observed. As a result, the amylase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
1
5
0
2
Order By: Relevance
“…These findings question the concept of strictly parallel secretion of pancreatic enzymes in humans, although the mechanisms underlying differential release of individual enzymes remain largely unknown. Potential mechanisms include selective changes of enzyme synthesis, selective intracellular transport and storage (17,18,69), and selective exocytosis or chemical modification of individual enzymes (89). A recent report supports the existence of different types of granules loaded with different proportions of enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings question the concept of strictly parallel secretion of pancreatic enzymes in humans, although the mechanisms underlying differential release of individual enzymes remain largely unknown. Potential mechanisms include selective changes of enzyme synthesis, selective intracellular transport and storage (17,18,69), and selective exocytosis or chemical modification of individual enzymes (89). A recent report supports the existence of different types of granules loaded with different proportions of enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report supports the existence of different types of granules loaded with different proportions of enzymes. Large granules containing a high proportion of trypsinogen and less amylase were selectively released in response to short-term cholecystokinin stimulation (18). Alternatively, differences in enzyme content among different compartments, i.e., peri-and teleinsular cells (52,76), and varying sensitivities of these compartments to stimulatory and inhibitory mediators (31) might explain nonparallel pancreatic enzyme secretion.…”
Section: Discussionmentioning
confidence: 99%
“…the peri-insular area [39]) or possibly even within individual cells. Upon stimulus-secretion coupling, there is also support for the differential release of contents [40]. Thus our results could indicate that IP3R-dependent mechanisms control the exocytosis of selective pools of ZGs that, for example, house relatively larger amounts of trypsinogen over amylase.…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, Rothman as well as others have shown that secretion of pancreatic enzymes can occur in a non-parallel fashion, so that the nature of the pancreatic juice does not correspond to a homogeneous mixture of all pancreatic enzymes. Selective discharge of certain proteins does occur under particular conditions of stimulated secretion (Adelson and Rothman 1975;Rothman 1976Rothman , 1981Dagorn, 1978;Adelson and Miller 1985;Sommer et al 1985;Rothman et al, 1991;de Dios et al 1999). On the other hand, Anderson, Jena, and colleagues (Anderson 2004;Jena 2004Jena , 2009) have introduced the concept of a discharge mechanism different from the classical exocytotic event (in which the entire granule fuses in one single event with the plasma membrane).…”
Section: Discussionmentioning
confidence: 99%